Evidence in the labor process - Arévalo Vela, Javier (2024)
This article develops the regulation of the evidentiary activity provided for in the New Labor Procedural Law. In this sense, the study of the three-dimensional theory of evidence; evidence as a fundamental right; the issue of the exclusion of evidence; the means of evidence admissible in the labor process; the opportunity to offer them and their performance; the exceptionality of ex officio evidence; the burden of proof and its reversal; evidence; what should be understood by evaluation of evidence; as well as presumptions in the labor process, in order to, finally, formulate the respective conclusions.